10-year Characteristics of Moisture Source Regions and Their Potential Effect on Seasonal Isotopic Signatures of δ18O in Tropical Trees of Southern Ecuador - Landshuter, Nadja; Mölg, Thomas; Grießinger, Jussi; Bräuning, Achim; Peters, Thorsten (Frontiers in Earth Science, 2020)
Ratios of stable oxygen isotopes in tree rings (18O) are a valuable proxy for reconstructing past climates. Such reconstructions allow us to gain better knowledge of climate dynamics under different (e.g. warmer) environmental conditions, which also forms the basis for effective risk management. The latter aspect is particularly relevant for our study site on the western flanks of the Andes in Southern Ecuador, since the region is frequently affected by droughts and heavy precipitation events during the rainy season (January to April), leading to enormous social and economic losses. In particular, we focus on precipitation amounts and moisture source regions as they are known to influence the 18O signature of tree rings. Moisture source regions are based on 240 h backward trajectories that were calculated with the trajectory model LAGRANTO for the rainy seasons 2008 to 2017. A moisture source diagnostic was applied to the air parcel pathways. The resulting moisture source regions were analyzed by calculating composites based on precipitation amounts, season, and calendar year. The precipitation amounts were derived from data of a local Automatic Weather Station (AWS). The analysis confirms that our study site receives its moisture both, from the Atlantic and the Pacific Oceans. Heavy precipitation events are linked to higher moisture contributions from the Pacific, and local SST anomalies along the coast of Ecuador are of higher importance than those off the coast towards the central Pacific. Moreover, we identified increasing moisture contributions from the Pacific over the course of the rainy season. This change and also rain amount effects are detectable in preliminary data of 18O variations in tree rings of Bursera graveolens. These signatures can be a starting point for investigating atmospheric and hydroclimatic processes, which trigger 18O variations in tree rings, more extensively in future studies.